Pendapat Mahasiswa Pendidikan Matematika Tentang Pembelajaran Online Dengan Menggunakan Pen Tablet Dan Aplikasi OneNote? - Irna Karlina Sensiana Blegur (Haumeni Journal of Education, 2022)
This study aims to determine the opinion of students of the Mathematics Education Study Program at the Nusa Cendana University about online learning using a pen tablet and the OneNote application. This is a quantitative descriptive study with a survey method. Data were collected using a Likert scale 1-5 questionnaire (strongly disagree-strongly agree) consisting of 10 positive statements as representatives of three indicators: conceptual understanding, usefulness and satisfaction, and student satisfaction in participating in the online lecture process. The data sources were one hundred and ten students of the Mathematics Education Study Program, FKIP Nusa Cendana University. Data analysis was carried out in 3 phases: calculating the cumulative score, calculating the assessment index, then proceeding with categorization according to the criteria. The results found are as follows: first, students agree that the use of these two tools contributes positively to several aspects of understanding concepts and students' convenience in participating in the online lecture process. Second, students strongly agree that the use of these two tools also contributes positively to several aspects of understanding concepts, convenience, and the usefulness and satisfaction of students in participating in the online lecture process when compared to online lectures without these two tools.